2021
DOI: 10.1016/j.bcp.2021.114499
|View full text |Cite
|
Sign up to set email alerts
|

MNK as a potential pharmacological target for suppressing LPS-induced acute lung injury in mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…We confirmed that this LDH level is comparable to the LDH level after the intranasal treatment of lipopolysaccharide (Fig. S1), which is generally used to induce lung injury ( 30 , 31 ). In addition, we observed massive neutrophil infiltration in the lungs 24 h after the Mp challenge using hematoxylin and eosin (H&E) staining ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…We confirmed that this LDH level is comparable to the LDH level after the intranasal treatment of lipopolysaccharide (Fig. S1), which is generally used to induce lung injury ( 30 , 31 ). In addition, we observed massive neutrophil infiltration in the lungs 24 h after the Mp challenge using hematoxylin and eosin (H&E) staining ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Severe lung infection, pulmonary contusion, and pulmonary embolism are the direct causes of ALI ( He et al, 2021 ). The main pathological features are acute inflammation and apoptosis of alveolar epithelial cells ( Allen and Kurdowska, 2014 ; Liu et al, 2020 ; Gao et al, 2021 ).…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 99%
“…19,20 In a mouse model of LPS-induced acute lung injury, MNK2 knockout resulted in reduced lung histopathological changes, decreased neutrophil counts, and diminished production of IL-6, TNF-α, and keratinocyte-derived chemoattractants in mouse bronchoalveolar lavage fluid. 21 In human keratinocytes, inhibition to MNK1 and the abolishment of eIF4E phosphorylation decrease the anisomycin-induced protein release of the pro-inflammatory cytokines TNF-α, IL-1β, and IL-6. 22 Furthermore, it has been proved that suppression of MNK2 in tumor-associated macrophages reprogrammed antiinflammatory macrophages toward a proinflammatory phenotype with the ability to activate CD8+ T cells that can resist tumor development.…”
Section: ■ Introductionmentioning
confidence: 99%